2019
DOI: 10.2298/vsp170516150n
|View full text |Cite
|
Sign up to set email alerts
|

Psychological characteristics in patients with non-cardiac chest pain

Abstract: Background/Aim. Chest pain of no heart origin resembles angina and when none medical reason is found, the patients are referred to psychiatrist for further assessment. The aim of this reserch was to determine psychological characteristics of the patients with non-coronary chest pain (NCCP), difference compared to the coronary patients and the predictive value of those parameters for NCCP. Methods. Fourty consecutively recruited patients without a diagnose of heart disease (NCCP group) were examined and compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In contrast with the present study, a study in Hong Kong and Wuhan from 2004 to 2005 reported that the quality of life and psychological impact in patients with NCCP were not different from CCP ( 27 ). In another study conducted in Niš, Serbia, although the patients with NCCP had no associated psychiatric disorder, coronary patients were more depressed and hostile ( 28 ). These results may be due to differences in the study population and the questionnaires used.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with the present study, a study in Hong Kong and Wuhan from 2004 to 2005 reported that the quality of life and psychological impact in patients with NCCP were not different from CCP ( 27 ). In another study conducted in Niš, Serbia, although the patients with NCCP had no associated psychiatric disorder, coronary patients were more depressed and hostile ( 28 ). These results may be due to differences in the study population and the questionnaires used.…”
Section: Discussionmentioning
confidence: 99%